Re-establishment of Begonia oxyphylla (Begoniaceae), a species from the coastal forests of Brazil - Jacques, Eliane De Lima (Phytotaxa, 2018)
Begonia oxyphylla A.DC. (Begoniaceae) is re-established at the rank of species, described and illustrated. This species was previously recognized as a variety of B. arborescens Raddi but is readily distinguished from that species by its tomentose-ferruginous indumentum, with shortly spinous stellate hairs (although some individuals may be glabrescent) and its elongated oblong leaf lamina with acuminate apices.